Ancient town tourism and the community supported entrance fee avoidance – Xitang Ancient Town of China. Issue 5 (3rd September 2021) - Su, Ming Ming; Yu, Jingjuan; Qin, Yueting; Wall, Geoffrey; Zhu, Yan
ABSTRACT: Ancient towns, embedded with traditional architecture, culture and life style, are popular tourism attractions worldwide. Tourism use often transforms residents' living spaces into shared multi-functional spaces for residents and tourists, which imposes impacts to residents and complicates community and tourism relationships. Entrance fees are widely used as an economic strategy for destination management and benefit re-distribution, triggering changes in relationships with profound implications socially and culturally. A framework is proposed to map relationships between stakeholders and flows of tourism impacts among key stakeholders in ancient town tourism. Readily accessible to a large urban population in the eastern developed area of China, Xitang Ancient Town in Jiaxing City of Zhejiang Province is one of the most famous tourism ancient towns in China. A mixed-methods approach involving both onsite and offsite data collections is used to explore and explain the enduring community support for the avoidance of entrance fee payments by tourists at Xitang Ancient Town. Limited access to tourism benefits for residents adjacent to the ticketing area is identified as the underlying reason for this. Practical suggestions are made to enhance community participation and ensure equitable access to tourism benefits for Xitang and ancient towns in China and elsewhere.